2019
DOI: 10.15252/embj.2018100727
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7a‐regulated translational readthrough of mammalian AGO 1 generates a micro RNA pathway inhibitor

Abstract: Translational readthrough generates proteins with extended C‐termini, which often possess distinct properties. Here, we have used various reporter assays to demonstrate translational readthrough of AGO1 mRNA. Analysis of ribosome profiling data and mass spectrometry data provided additional evidence for translational readthrough of AGO1. The endogenous readthrough product, Ago1x, could be detected by a specific antibody both in vitro and in vivo. This readthrough process is directed by a cis sequence downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 52 publications
(111 reference statements)
3
42
0
Order By: Relevance
“…Alternative decoding of factors that regulate gene expression could consequentially result in broad changes in downstream processes. For example, SCR of the mammalian gene for Argonaute1 (Ago1) produces the Ago1x isoform, which acts as a competitive inhibitor of the miRNA pathway, leading to increased global translation as a result of SCR [ 12 ]. In the present work, a deletion that abolished the C-terminal extension had strong effects on the transcriptional profile of dfr 14 mutant larvae, with pronounced effects on genes involved in gene expression, neural proliferation, sensory organ development, and immune system processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative decoding of factors that regulate gene expression could consequentially result in broad changes in downstream processes. For example, SCR of the mammalian gene for Argonaute1 (Ago1) produces the Ago1x isoform, which acts as a competitive inhibitor of the miRNA pathway, leading to increased global translation as a result of SCR [ 12 ]. In the present work, a deletion that abolished the C-terminal extension had strong effects on the transcriptional profile of dfr 14 mutant larvae, with pronounced effects on genes involved in gene expression, neural proliferation, sensory organ development, and immune system processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 was shown to bind to a cis -acting element in VEGF-A 3′ untranslated region (UTR) and promote SCR [ 11 ]. Translational readthrough of the mammalian AGO1 gene, encoding the Argonaute 1 (Ago1) protein, was recently found to be positively regulated by the let-7a miRNA upon binding 3′ of the canonical stop codon [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the AGO1x protein isoform was described, product of the translational stop read-through of AGO 1 transcripts induced by the expression of the Let7a miRNA. Ectopic expression of AGO1x acts as a negative competitor of the miRNA pathway 36 . A hypothesis would be that mutated AGO1 proteins may act as the AGO1x isoform through competitive inhibition of wild type AGO proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, AGO1 has also been detected as a candidate for programed translational readthrough, a process generating longer isoforms by continuing translation beyond the stop codon (Eswarappa et al, 2014). Two recent studies demonstrated the presence of this translational readthrough product of AGO1 in cells, termed AGO1x (Ghosh et al, 2019;Singh et al, 2019). AGO1x is a protein isoform, which is 33 amino acids longer than AGO1 (Figure 1A).…”
Section: Structure and Domains Of The Argonaute Proteinsmentioning
confidence: 99%
“…Since AGO1x is incapable of interacting with GW182, it cannot induce translational repression. It is therefore thought that AGO1x competes with the canonical miRNA pathway and thereby leads to reduced posttranscriptional repression of target mRNAs (Singh et al, 2019). Second, in breast cancer cells, AGO1x has been shown to prevent the accumulation of dsRNAs and thereby suppresses the interferon response in these cells, a function independent of the canonical miRNA pathway (Ghosh et al, 2019).…”
Section: Structure and Domains Of The Argonaute Proteinsmentioning
confidence: 99%